Stilistiniai būsimojo laiko atitikmenys lietuvių ir anglų kalbose - Steponavičiūtė, I. (Kalbotyra, 1976)
This paper presents certain modal and stylistic aspects of tense forms and constructions by which future activities and states are indicated in Lithuanian and English.Both languages offer a choice of diverse forms for expressing future events which admits of a wide range of solutions. Apart from its basic use the future tense form may be used in a subjective function. When used for future time reference, the present tense forms fulfil analogous stylistic functions in both languages. Some forms should be considered as having no analogous form in the receptor language.The nonexistence of a corresponding form in the receptor language does not presuppose the impossibility of transferring the entire conceptual and expressive information contained in that form. It can be carried by other formal features which fulfil a function equivalent to that of the original form.